Strategic Performance Dynamics: Elucidating the Effect of Competitive and Growth Strategies on Companies - Armalia Reny W.A. (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
There was a dearth of empirical information and thorough understanding into how these strategies interacted and affected the performance of companies in the setting of Lampung Province before this research. Thus, this research investigates the effect of competitive and growth strategies on the strategic performance of companies registered with the Lampung Province Department of Industry and Trade. Utilizing a quantitative approach and statistical analysis of data from 396 survey respondents representing businesses across 15 cities and regencies in Lampung Province, the study employs the Partial Least Square (PLS) Structural Equation Modeling (SEM) method with SmartPLS software to analyze the data. The results indicate that competitive strategy significantly affects the strategic performance of companies. Additionally, growth strategy also significantly contributes to improved strategic performance, highlighting the importance of selecting the right growth strategies for companies. Simultaneously, both competitive and growth strategies exert a significant effect on the strategic performance of companies. These insights provide valuable guidance for businesses and regulatory authorities in Lampung Province's industrial and trade sectors, aiding them in designing more effective strategies to enhance company performance, considering both competitive and growth strategies.